Neurosurgical intensive care unit - essential for good outcomes in neurosurgery? - Lang, Josef Michael; Meixensberger, Jürgen; Unterberg, Andreas; Tecklenburg, Andreas; Krauss, Joachim K. (Langenbeck's archives of surgery, 2011)
Neurosurgical intensive care units were increasingly agglomerated in large centralized interdisciplinary intensive care units in the last two decades. In the majority, these centralized interdisciplinary intensive care units were directed and managed by intensivists coming from anaesthesiology. We sought to review the evidence supporting neurosurgical intensive care as a highly specialized discipline resulting in benefits for the treated patients.
Gesehen am 12.07.2022